Stabilization Policies in Developing Countries with a Parallel Market for Foreign Exchange : A Formal Framework - Agenor, Pierre-Richard (IMF Working Papers; Working Paper ;, 1990)
The paper develops and tests a model of a developing economy that incorporates trade and capital restrictions, illegal transactions, a parallel foreign exchange market, currency substitution features, and forward-looking rational expectations. Temporary expansionary demand policies are associated with an increase in output and prices, a fall in the stock of net foreign assets, and a depreciation of the parallel exchange rate. The speed of adjustment is inversely related to the degree of rationing in the official foreign currency market. A once-for-all devaluation of the official exchange rate has no long-term effect on the premium.